Penggunaan Video Penutur Asli Berbasis Tahapan Pra-Saat-Pasca Menonton dalam Meningkatkan Keterampilan Kalam Siswa Madrasah - Arum Rayana; Ilma Hannisa' (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to analyze the effectiveness of native speaker video based pre-while- and post viewing stages in improving students’ Arabic speaking skills. The research employed a Classroom Action Research design conducted in two cycles involving seventh-grade students of MTs Sadamiyah Jepara. Data were collected through observation, oral tests, and student perception questionnaires. The results revealed a significant improvement in the mean score from 58.3 in Cycle I to 86.2 in Cycle II. All speaking aspects pronunciation, grammar, vocabulary, fluency, and comprehension showed substantial progress. The N-Gain score of 0.67 indicates a moderate-to-high level of effectiveness. The findings suggest that pedagogically structured native speaker videos, supported by vocabulary reinforcement, significantly enhance students’ speaking competence and classroom engagement.